HAMBATAN KOMUNIKASI ANTAR BUDAYA MAHASISWA RAGAM ETNIS DI ASRAMA MAHASISWA IAHN GDE PUDJA MATARAM - Kartika, Komang Reza; Astraguna, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
This study aims to uncover and understand the various barriers to intercultural communication faced by students at the IAHN Gde Pudja Mataram Student Dormitory. As a higher education institution with a significant diversity of ethnicities and cultures among its students, the dormitory presents a unique social dynamic. However, this diversity can lead to conflict if not managed properly. The research uses a qualitative approach, employing data collection techniques such as participatory observation, semi-structured interviews, and document analysis. The findings reveal that factors such as language differences, social norms, ethnocentrism, and a lack of cultural awareness are the primary causes of intercultural communication barriers at the dormitory. Students tend to interact mostly within their own ethnic groups, avoiding communication with those from other ethnic backgrounds, which often leads to misunderstandings and prejudice. Moreover, a closed attitude and a lack of respect for cultural differences further worsen the social atmosphere within the dorm. The study concludes that initiatives from both students and dormitory management are needed to foster cultural understanding, enhance empathy, and create opportunities for cross-ethnic interactions in order to promote a better social harmony. The findings are expected to provide guidance for developing more effective intercultural communication policies in multicultural higher education environments.